Public Response to Online Public Debate in the 2020 Regional Head Election of Ponorogo Regency - Alifa Chandra Kumara; Dian Suluh Kusuma Dewi (Budapest International Research and Critics University, 2021)
This year, regional head elections were held in the midst of the Covid-19 pandemic so that social media can be used as a means of online campaigns to reduce mass gathering. This research was conducted to see the response of the Ponorogo community in participating in online public debates and to assess people's political participation by analyzing public comments on public debate shows on YouTube and Facebook. The data is processed using the Nvivo12 plus application by using cross tabulation data analysis techniques with manual coding then the results of the data obtained are described and analyzed in accordance with the theory of response and political participation. The data obtained on Facebook and YouTube were 772 responses with details of 357 responses on Facebook and 415 responses on YouTube. The responses given are in the form of positive, negative, and neutral responses. The process of obtaining data on public response is in accordance with the S-O-R response theory (Stimulus, Organism, Response) and the stage of response formation, as well as the political participation of the Ponorogo community is high enough to see the debate shows but the level of activeness in giving responses is less active.